A Pilot Study to Explore Patient Satisfaction With a Virtual Rehabilitation Program in Multiple Sclerosis: The RehabVR Study Protocol - Meca-Lallana, Virginia; Prefasi, Daniel; Alabarcez, Walter; Hernández, Teresa; García-Vaz, Fabiola; Portaña, Angélica; Gomis, David; Téllez, Nieves; García-Bernáldez, Cristina; Mauriño, Jorge; Medrano, Nicolás; Vázquez-Doce, Aránzazu (Frontiers in Neurology, 2020)
Background: Virtual reality (VR) has emerged as a promising treatment approach in rehabilitation for patients with multiple sclerosis (MS) due to its potential to increase patient motivation and rehabilitation adherence. One of the key features for rehabilitation adherence is patient satisfaction with the VR rehabilitation (VRR) program, and information on user satisfaction and not only effectiveness is required to systematically include VRR in routine clinical practice. Given that information on patient satisfaction with VRR is scarce, the primary objective of this study is to assess long-term patient satisfaction with a novel VRR program. This program has been specifically designed for MS patients by a multidisciplinary team of specialists, based on an effective conventional rehabilitation (CR) program. Secondarily, discomfort with VRR will be evaluated, and therapy adherence and changes in a variety of domains typically affected by MS will be compared between patients receiving VRR and patients receiving CR. Methods: In this prospective single-center 6-month follow-up study, 32 and 16 MS patients will receive VRR or CR, respectively. Patients will attend twice weekly rehabilitation sessions on site during 4 weeks, and they will continue with rehabilitation at home for 5 additional months. Satisfaction, assessed by the User Satisfaction Evaluation Questionnaire (USEQ), at 6 months of the VRR program initiation will be the primary outcome. Secondary outcomes include adherence, disability, spasms and spasticity, balance, fatigue, activities of daily living (ADLs), depression, anxiety, work status, cognition, demographic and clinical characteristics (in the VRR and CR groups), and discomfort (in the VRR group). Outcome measures will be assessed at baseline, and at 1 and 6 months of rehabilitation initiation. Discussion: The study is intended to provide a better understanding of long-term patient satisfaction with a VRR program specifically designed for MS patients. Additionally, the study will provide information on long-term adherence, changes in motor symptoms, cognitive functions and patient-reported outcomes after the rehabilitation program. The results from this study will help to gather valuable knowledge on the use of rehabilitation with a new VR tool in MS patients.